Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1136/thx.52.5.422
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Pneumocystis carinii from patients to hospital staff

Abstract: Abstractimmunodeficient patients. 10-13 P carinii DNA has recently been detected in air filters from Background -An extrahuman reservoir of human pathogenic Pneumocystis carinii animal facilities housing immunosuppressed rats with P carinii pneumonia (PCP) as well as remains unknown. Host to host transmission has been described in animal from air filters from inpatient and outpatient rooms in hospital departments treating patients studies and in cluster cases among immunodeficient patients. P carinii DNA has w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…P. carinii DNA has not generally been found in these types of noninvasive respiratory tract samples in either immunocompromised or immunocompetent individuals without P. carinii pneumonia (30). Previous studies examining serum titers of P. carinii antibodies in HCW have shown conflicting results (20,22), and in one of the studies P. carinii DNA was not detected in oropharyngeal washings from contact HCW (22), but this may be explained by the use of a single round rather than nested PCR.…”
Section: Discussionmentioning
confidence: 76%
“…P. carinii DNA has not generally been found in these types of noninvasive respiratory tract samples in either immunocompromised or immunocompetent individuals without P. carinii pneumonia (30). Previous studies examining serum titers of P. carinii antibodies in HCW have shown conflicting results (20,22), and in one of the studies P. carinii DNA was not detected in oropharyngeal washings from contact HCW (22), but this may be explained by the use of a single round rather than nested PCR.…”
Section: Discussionmentioning
confidence: 76%
“…Relatively few organisms (10-100 cysts) are needed to cause infection in immunocompromised animals [42]. Epidemiologic studies and reports of clusters of infection in oncology centers and in renal transplant recipients support the acquisition of infection from environmental or human sources [43][44][45][46][47]. Molecular studies in animals and humans, using a variety of genetic probes, have suggested that both reinfection and reactivation of latent infection are significant factors in disease incidence [48,49].…”
Section: Pathogenesis Of Infectionmentioning
confidence: 99%
“…Studies of health care workers have examined either anti-Pneumocystis antibody responses or colonization with Pneumocystis as determined by detection of Pneumocystis DNA by PCR of oral or nasal samples. Although some studies have found no measurable difference in antibody titers in health care workers exposed to PCP, others have detected increases in those with PCP exposure (176,186). A recent study of antibodies to the major surface glycoprotein (Msg) of Pneumocystis found that those individuals with a clinical occupation (and presumed exposure to PCP) had higher antibody levels to Msg fragments that nonclinical workers without PCP exposure (288).…”
Section: De Novo Infectionmentioning
confidence: 99%
“…As discussed above, colonized animals can transmit colonization to other animals and can also transmit disease to immunocompromised hosts (4,99). Evidence of person-to-person transmission of PCP as well as detection of colonization in health care workers suggests that the organism might pass through a colonized host before causing disease (56,57,94,176,186,215,288).…”
Section: Role In Diseasementioning
confidence: 99%